2017
DOI: 10.1111/anu.12643
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary inclusion of yacon, ginger and blueberry on growth, body composition and challenge test of juvenile rockfish (Sebastes schlegeli ) against Edwardsiella tarda

Abstract: Effects of dietary inclusion of yacon, Polymnia sonchifolia (YC), ginger, Zingiber officinale (GG), and blueberry, Vaccinium ashei (BB), on growth, body composition and challenge test of rockfish against Edwardsiella tarda compared to ethoxyquin were investigated. Three hundred and sixty fish were randomly distributed into 12 flowthrough tanks. Four experimental diets were prepared: the control diet (Con) with 0.1 g/kg ethoxyquin, and YC, GG and BB diets. Each diet was assigned to triplicate tanks of fish and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…Groups fed E. globulus extract recorded significantly higher levels of protein content in the whole body. This is similar to study by Kim et al (2018) which reported significantly higher carcass protein content in juvenile rockfish (Sebastes schlegeh). Also, the protein content recorded in this study confirm previous report by Mohammadi et al (2020) which documented higher values of carcass protein in common carp (Cyprinus carpio) fed ginger extracts.…”
Section: Effects Of E Globulus On Whole Body Proximate Compositionsupporting
confidence: 91%
“…Groups fed E. globulus extract recorded significantly higher levels of protein content in the whole body. This is similar to study by Kim et al (2018) which reported significantly higher carcass protein content in juvenile rockfish (Sebastes schlegeh). Also, the protein content recorded in this study confirm previous report by Mohammadi et al (2020) which documented higher values of carcass protein in common carp (Cyprinus carpio) fed ginger extracts.…”
Section: Effects Of E Globulus On Whole Body Proximate Compositionsupporting
confidence: 91%
“…This finding is consistent with our previous study, in which the proximate composition of juvenile S. schlegelii was not significantly affected by diet supplementation with 1% GRJE [ 34 ]. In contrast, Kim et al [ 33 ] reported significantly higher crude protein, crude lipid, and moisture content in juvenile S. schlegelii fed 1% dried ginger for 8 weeks. Additionally, juvenile Cyprinus carpio fed varying doses of ginger extract showed significant differences in carcass composition [ 6 ].…”
Section: Discussionmentioning
confidence: 93%
“…Supplementing fish diets with various types (powder, extract, oil, by-product, etc.) of ginger ( Zingiber officinale ) has been demonstrated to enhance fish performance [ 2 , 16 , 32 , 33 , 34 ]. In our previous study, we showed that dietary GRJE supplementation significantly improved juvenile black rockfish growth performance, innate immunity, and disease resistance against Gram-negative bacteria V. harveyi [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of documents have shown that herbs and natural plants improved growth performance, enhanced immunity and increased disease resistance in aquaculture [ 43 , 44 , 45 ]. The present study demonstrated that diets supplemented with 75–150 mg/kg andrographolide increased growth and decreased the feed conversion rate in M. albus .…”
Section: Discussionmentioning
confidence: 99%